Study on System Design and Integration of Variable Buoyancy Systems for Underwater Operation - Tiwari, B. K.; Sharma, R. (Defence Science Journal, 2021)
This paper presents the design and analysis of the ‘Variable Buoyancy System (VBS)’ for depth control which is an essential operation for all underwater vehicles. We use the ‘Water Hydraulic Variable Buoyancy System (WHVBS)’ method to control the buoyancy and discuss details of the system design architecture of various components of VBS. The buoyancy capacity of the developed VBS is five kilograms and the performance of the VBS in standalone mode is analysed using numerical simulation. Presented VBS is operable to control the buoyancy up to sixty meters of depth and it can be directly installed to medium size UVs. Simulation results show that the developed VBS can reduce the energy consumption significantly and higher in each cycle (i.e. descending and ascending) of the same VBS in standalone mode being operated with either propeller or thruster for sixty meters depth of operation. Our results conclude and demonstrate that the designed VBS is effective in changing the buoyancy and controlling the heave velocity efficiently and this serves the purpose of higher endurance and better performances desired in rescue/attack operations related to the UVs both in civilian and defense domains.